PROBLEM RECYCLABLE RAW MATERIALS BOTH DIRECTIONS OF RESEARCH IN STUDENTS’ SCIENTIFIC CIRCLES CONDITIONS - Назарчук, А.О.; Погоріла, І.О. (World of Medicine and Biology, 2015)
The article deals with the problem of attracting medical students in research activities within the scientific circle. Environmental subjects research are being discussed. The role of the leader in the formation of ecological thinking, scientific outlook, ecological culture are being analyzed.